2019
DOI: 10.1101/799700
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of SRSF3 splicing factor in generating circular RNAs

Abstract: Circular RNAs (circRNAs) represent a novel class of non-coding RNAs that are emerging as potentially important regulators of gene expression. circRNAs are typically generated from host gene transcripts through a non-canonical back-splicing mechanism, whose regulation is still not well understood. To explore regulation of circRNAs in cancer, we generated sequence data from RNase R-resistant transcripts in human p493-6 B-lymphoid cells and identified thousands of novel as well as previously identified circRNAs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In addition, base pairing between Alu elements and dimerization of RBPs in introns play essential regulatory roles in the formation of circRNAs alternative splicing [33,42]. For example, the protein HQK is encoded by quaking (QKI) [43], fused in sarcoma (FUS) [44], and serine/arginine-rich splicing factor 3 (SRSF3) [45]. Via the Mini gene reporting system constructed in Drosophila cells, Liang et al found that the trans splicing factor SR protein and heterogeneous nuclear ribonucleoproteins (hnRNPs) could interact with intron repeat sequences.…”
Section: Biological Origin Of Circrnasmentioning
confidence: 99%
“…In addition, base pairing between Alu elements and dimerization of RBPs in introns play essential regulatory roles in the formation of circRNAs alternative splicing [33,42]. For example, the protein HQK is encoded by quaking (QKI) [43], fused in sarcoma (FUS) [44], and serine/arginine-rich splicing factor 3 (SRSF3) [45]. Via the Mini gene reporting system constructed in Drosophila cells, Liang et al found that the trans splicing factor SR protein and heterogeneous nuclear ribonucleoproteins (hnRNPs) could interact with intron repeat sequences.…”
Section: Biological Origin Of Circrnasmentioning
confidence: 99%
“…Besides this, the RNA binding protein (RBP) is an important factor in regulating the production of circRNA. RBP can specifically bind to the flanking introns at both ends of RNA, acting as an RBP while narrowing the distance between the splice recipient and the donor, resulting in the formation of circRNAs (Naqvi et al, 2019; with U1 small nuclear ribonucleoproteins and then increase the transcription of their host genes by binding with RNA pol II; ciRNA, and the RNA pol II complex can directly interact and play a role in regulating parental gene transcription. (e) CircRNAs can be translated into peptides or proteins.…”
Section: The Biogenesis Of Circrnasmentioning
confidence: 99%
“…Besides this, the RNA binding protein (RBP) is an important factor in regulating the production of circRNA. RBP can specifically bind to the flanking introns at both ends of RNA, acting as an RBP while narrowing the distance between the splice recipient and the donor, resulting in the formation of circRNAs ( Naqvi et al, 2019 ; Pagliarini et al, 2020 ; Zhao et al, 2020 ). It is well-known that CDR1as, as an antisense transcript of cerebellar degeneration associated protein 1, can be used as a specific circRNA of miR-7, so it is also known as CIRS-7.…”
Section: Overview Of Circrnasmentioning
confidence: 99%